Aspectos da gestão da mudança na implementação de um sistema de gestão de SMS: um estudo de caso - Estrada, José Alexandre Ferreira Duque (2011)
There are currently many tools for the implementation and maintenance of HSE management systems, and it may be even stated that top managements of large companies are committed to achieving a good result in the HSE performance, considering the level of awareness already achieved, the demands of the market and the development of legislation in this area. However, in order to assure that systems are in place and reach the entire workforce, relevant aspects of change management should be considered which, when overlooked, may lead to poor implementation and performance. This study focuses on change management issues as supporting tools to the full Implementation HSE management systems. This analysis was carried out through a case study of an energy company, engaged in exploitation and production of gas and petroleum. To do so, we analyzed the guidelines, standards and procedures adopted by the company, reviewed the operational discipline and change management concepts, and hence provided suggestions for creating value to the company s HSE Management System, seeking the engagement of the entire workforce in the use of the procedures established